'Instruments for Everyone': Empowering disabled creators with tools for musical expression. - Rodrigues, Paulo Maria; Gehlhaar, Rolf; Girao, Luis Miguel; Penha, Rui (Ubiquity (2045-6271), 2012)
This article reports a project commissioned by the Education Service of Casa da Música (CdM) in which tools were developed to allow musical expression by physically and mentally challenged people. The first phase involved defining a group of clients, identifying their capabilities and motivations and designing customized solutions involving different combinations of software and hardware. The second phase consisted of a programme of regular activities using these resources in their institutions. The third phase involved the composition of a piece of music using those resources along with others and its performance by these people in the main concert hall of CdM in April 2010. 'Viagem', a piece written for, and performed by, a group of about 80 people with mixed abilities proved the concept, but it was, above all, a deep artistic experience.